Holy Ghosts : The Christian Century in Modern Japanese Fiction - Suter, Rebecca, 1975- (Book collections on Project MUSE., 2015)
This work examines the popularity of the Christian century in modern Japanese fiction and reflects on the role of crosscultural representations. Exploring the twentieth century's fascination with the Christian century enables Rebecca Suter to reflect on modern Japan's complex combination of Orientalism, self-Orientalism, and Occidentalism.